Implementation of Differentiated Learning in Science Subject in Grade V of SD Negeri 03 Geragahan - Rudi Harianto; Rayendra; Alwen Bentri; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2026)
The diversity of student characteristics is a challenge for educators in the learning process. Therefore, the ability of teachers to accommodate these differences is a key factor in creating effective and meaningful learning. Differentiated learning has emerged as an adaptive and meaningful approach. Differentiated learning has emerged as an adaptive approach designed to optimally meet students' learning needs. This study aims to describe the implementation of differentiated learning in science subjects in class V of SD Negeri 03 Garagarhan, focusing on three main aspects, namely planning, implementation, and learning assessment. This research uses a qualitative approach with descriptive methods. Data were collected through interviews, observations, and documentation with instruments in the form of interview guidelines, observation guides, and documentation. Data analysis techniques were carried out through the stages of data reduction, data presentation, and drawing conclusions. The implementation of differentiated learning in science subjects in class V of SD Negeri 03 Geragahan has been carried out in a structured and collaborative manner. Planning involves teachers, principals, and parents by considering the learning needs of students from academic and socio-cultural aspects. The implementation begins with a diagnostic assessment and is outlined in a teaching module that adjusts the learning method, media, and environment. Assessment is carried out in a sustainable and adaptive manner. However, this process still faces obstacles such as time constraints, as well as the potential for social jealousy between students. Nevertheless, the school still shows a commitment to realizing inclusive and student-centered learning.